Management of Christian Entertainment in Semarang (Jurnal Seni Musik, 2023)
Christian Entertainment is a music group from Semarang that manages its management to maintain its existence and music quality. This is evidenced by the participation of Christian Entertainment in the entertainment industry and music performances, especially in wedding events, from 1999 until now. The purpose of this research was to understand and describe the performance management of Christian Entertainment and identify the factors that hinder and support the management activities carried out by the group. This research is a descriptive study with a qualitative approach. Data collection techniques employed in this study included observation, interviews, and documentation. Data validity was ensured through triangulation. Christian Entertainment, in terms of management functions, involve planning, organizing, directing, and controlling. The elements of Christian Entertainment's management include man, material, method, machine, market, and money. The management principles applied by Christian Entertainment are division of labor, delegation of rights and responsibilities, and unity of direction. The lack of a dedicated rehearsal space poses a challenge to the management activities conducted by Christian Entertainment Music Group. .